ESA EO Data Preservation System. (7th May 2020) - Albani, Mirko; Douzal, Michel; Castrovillari, Domenico; Boezi, Paolo; Iozzino, Daniele; Maggio, Iolanda
The European Space Agency (ESA) has the mandate to assure the long-term preservation, sharing and exploitation of space data and its associated knowledge. ESA's aim is to turn space exploration and space-related activities into an overall societal project involving a wide variety of stakeholders. To this end, it brings together and coordinates as many countries as possible under the banner of space missions. It is a basic principle that ESA deals with its stakeholders openly and with real transparency, an approach that has contributed to its long-term success. The Earth Observation (EO) Data Preservation System has the main objective of providing the required infrastructure and services to assure ESA and Third Party Missions (TPM) EO Data Records and Associated Knowledge preservation and accessibility, and to support the cooperation activities with national and international organizations in the data preservation domain. The generic "EO Missions/Sensors Preserved Dataset" content includes Data Records and Associated Knowledge.